The Peer Tutor Model with Cognitive Conflict Strategies in Collaborative Learning Mathematical Problem Solving and Its Effect on Individual Achievement. - Rusmini Rusmini; Muhammad Rizky Mazali; Fitrah Sari Wahyuni Harahap; Ermayanti Astuti (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Cognitive conflict is a condition where students encounter new experiences that are not neatly arranged in their cognitive structure. The process of assimilation between old and new concepts in students' cognition. The assimilation process is more effective when done together with peer tutors. The purpose of this study was to see the effect of cognitive conflict on collaborative mathematical problem solving and its effect on individual learning success. Case study research methods, descriptive qualitative and quantitative. Learning is carried out to 28 semester II students collaboratively in solving integral problems. Pretest knowing the initial ability of mathematics, given the problem of integral functions of fractional powers. Given posttest independently. In the learning process students with low initial abilities and difficult to ask questions with peer tutors dare to ask information that has just been received with the help of students with moderate and high initial abilities. Cognitive conflict strategies with peer tutors are very useful. The impact of the experience of peer tutors, posttest results is very significant. This means that the posttest results increased significantly for the material of integral functions of fractional powers and motivation to learn for the better.